Digital Storytelling Media to Increase Creativity in Dance Creation on Simple Dance Movement Exploration Material - Rendi Prianto; Atip Nurharini (Universitas Pendidikan Ganesha, 2023)
The lack of student interest and interest in learning dance as well as the lack of relevance in student interest results in low student creativity in creating dance movements in dance learning. The aim of this research is to develop innovative digital learning media, the feasibility of learning media, and the effectiveness of the media to increase the creativity of dance creation in simple dance movement exploration material in class II elementary schools. This research uses the Research and Development (R&D) method with the ADDIE model. The data collection techniques used in this research are observation, interviews, questionnaires and tests. Class II elementary school students are the population. Then, the data analysis technique uses qualitative descriptive analysis techniques and quantitative analysis techniques, as well as inferential statistics. The results of this research can be obtained from expert tests, namely, high category material expert test, high category media expert test, high category class teacher test, high category small group test, high category large group test. Then, the results of the n-gain test stated that the media had been developed digital storytelling.It can be said to be quite effective in increasing the creativity of dance creation. Based on this statement, digital storytelling media is good to use, effective, and quite suitable for use in learning dance movement exploration material in simple dance movement exploration material in class II elementary schools and is able to create dance creativity in students.